Examining the relationship between effective organizational factors and organizational agility - Namjoo, Farhad; Jafari, Mohammad Bagher (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2021)
Background and purpose: The main issue in this research is to examine the relationship between some organizational variables (such as emotional intelligence, organizational intelligence, and intellectual capital management) and organizational agility. Considering this importance, the researcher has decided to examine the relationship between some organizational variables as predictor variables in the criterion variable (organizational agility) to investigate the relationship between effective organizational factors and organizational agility. Methodology: The current research is descriptive and correlational. The statistical population is all the managers of government offices in Yasouj, which were more than 200 people. From this number, 127 people were selected using the stratified random sampling method, and questionnaires on organizational agility, emotional intelligence, organizational intelligence, and intellectual capital management were provided to them. Results: The data was collected, and using Pearson, Spearman, and multiple regression statistical methods, it was observed that there is a significant relationship between the dimensions of these variables and in predicting the organizational agility variable, self-management with a beta value (0.326), application of knowledge with beta value (0.282), unity and agreement with beta value (0.268), and relational capital with beta value (0.229), have a more positive effect compared to other variables. Conclusion: the managers of government departments can improve the infrastructures, including flexible organizational structure, by creating new strategies; Delegation of authority to experts; effective training of employees; fast response; rapid allocation of resources; strategic vision; improving quality; providing value to the customer; risk management capability; Employee participation; Capable and multi-skilled employees and flexible employees increase their agility capabilities.